Aluminium vacuum arc plasma application for intermetallic layers formation using plasma immersion ion implantation method; Известия вузов. Физика; Т. 57, № 12/3 - Ryabchikov A. I. Aleksandr Ilyich (2014, 2014)
Заглавие с экрана